Montgomery and informed consent during Covid-19: Pneumatic retinopexy versus pars plana vitrectomy or scleral buckling for retinal detachment repair. (June 2021) - Kiew, G; Poulson, AV; Newman, DK; Alexander, P; Snead, MP
Recent reports suggest that the use of an outpatient-based procedure (pneumatic retinopexy, PR) for retinal detachment repair should be encouraged within the UK, especially in light of Covid-19 and possible restrictions/competing demands on access to operating theatres. It is therefore essential that patients receive comprehensive information about the risks and benefits of this approach compared with a formal surgical repair either by pars plana vitrectomy (PPV) and/or scleral buckling (SB). We report a retrospective case series of retinal detachments (RD) satisfying the strict selection criteria for PR but who were managed with formal surgery. Single-operation success rate for PPV/SB at six months follow-up was 93.8% in our study, higher than published primary success rates for PR (60–80%). When counselling patients for possible PR, the ease, speed and potentially reduced co-morbidity of an outpatient-based procedure needs to be balanced against its significantly higher failure rate in comparison with primary PPV/SB.